A resting‐state fMRI study of obese females between pre‐ and postprandial states before and after bariatric surgery. (1st November 2016) - Wiemerslage, Lyle; Zhou, Wei; Olivo, Gaia; Stark, Julia; Hogenkamp, Pleunie S.; Larsson, Elna‐Marie; Sundbom, Magnus; Schiöth, Helgi B.
Abstract: Past studies utilizing resting‐state functional MRI (rsfMRI), have shown that obese humans exhibit altered activity in brain areas related to reward compared to normal‐weight controls. However, to what extent bariatric surgery‐induced weight loss alters resting‐state brain activity in obese humans is less well‐studied. Thus, we measured the fractional amplitude of low‐frequency fluctuations from eyes‐closed, rsfMRI in obese females ( n  = 11, mean age = 42 years, mean BMI = 41 kg/m 2 ) in both a pre‐ and postprandial state at two time points: four weeks before, and four weeks after bariatric surgery. Several brain areas showed altered resting‐state activity following bariatric surgery, including the putamen, insula, cingulate, thalamus and frontal regions. Activity augmented by surgery was also dependent on prandial state. For example, in the fasted state, activity in the middle frontal and pre‐ and postcentral gyri was found to be decreased after surgery. In the sated state, activity within the insula was increased before, but not after surgery. Collectively, our results suggest that resting‐state neural functions are rapidly affected following bariatric surgery and the associated weight loss and change in diet. Abstract : Resting‐state functional MRI (rsfMRI) was measured in both the fasted and postprandial state, in obese females before and after bariatric surgery. Neural activity was rapidly altered following surgery, and changes were also dependent on prandial state. Affected areas included the putamen, insula, cingulate, thalamus and frontal regions.